(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
The impact of the COVID-19 outbreak is being endured throughout the world, and the European Union (EU) is no exception. The rapid spreading of the virus effected, among other things, restriction on the freedom of movement. The EU member states introduced national response measures to contain the pandemic and protect public health. While broadly similar, the measures differ with regard to strictness and the manner of introduction, reflecting the political legitimacy of the respective country. With the ‘Guidelines concerning the exercise of the free movement of workers during COVID-19 outbreak’ – its first COVID-19-related Communication – the European Commission (EC) attempted to curb differing practices of the EU member states and ensure a coordinated approach. Ultimately, this action was aimed at upholding of fundamental rights as guaranteed to EU citizens, one such being the freedom of movement. Thus, from the very start of the pandemic, the coordinated actions of EU institutions sought to contain the spread of COVID-19 infections with the support and cooperation of EU member states. This is confirmed by the most recent Council of the EU (Council) recommendation on a coordinated approach to restrictions to freedom of movement within the EU of October 2020. While they did prevent the spread of infection and save countless lives, the movement restriction measures and the resulting uncertainty have greatly affected the people, the society, and the economy, thereby demonstrating that they cannot remain in force for an extended period. This paper examines the measures introduced by EU member states and analyses the legal basis for introducing therewith limitations on human rights and market freedoms. To what extent are the EU and member states authorized to introduce restrictions on the freedom of movement in the interest of public health? Have the EU and member states breached their obligations regarding market freedoms and fundamental rights under the Treaty? And most importantly: have they endangered the fundamental rights of the citizens of the EU?